2019
DOI: 10.1002/adma.201903480
|View full text |Cite
|
Sign up to set email alerts
|

Are Cu2Te‐Based Compounds Excellent Thermoelectric Materials?

Abstract: With the increasingly serious environmental pollution and intensified energy crisis, exploitation and utilization of new kinds of clean energy resources are imperative. Among them, thermoelectric (TE) conversion technology based on highperformance TE materials enables direct energy conversion between heat and electricity through the movement of internal phonons and charge carriers. [1][2][3][4] It has shown extensive and important prospects in power generation using industrial waste heat and electronic refrige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 82 publications
(87 reference statements)
1
65
0
Order By: Relevance
“…Such a phenomenon has also been observed in many classic thermoelectric materials, including PbX, Bi 2 X 3 , Cu 2 X, SnX (X = S, Se). [ 16,17 ] Although β ‐CsCu 5 Se 3 shows great performance in photovoltaic applications, [ 15,18 ] the research on its lattice thermal conductivity and thermoelectric properties has not been reported yet, which motivates us to carry out this study. On the basis of density functional theory (DFT) combined with semiclassical Boltzmann transport theory, we do find that β ‐CsCu 5 Se 3 possesses ultralow lattice thermal conductivities and a high ZT value, besides the reported photovoltaic features, exhibits high thermoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“…Such a phenomenon has also been observed in many classic thermoelectric materials, including PbX, Bi 2 X 3 , Cu 2 X, SnX (X = S, Se). [ 16,17 ] Although β ‐CsCu 5 Se 3 shows great performance in photovoltaic applications, [ 15,18 ] the research on its lattice thermal conductivity and thermoelectric properties has not been reported yet, which motivates us to carry out this study. On the basis of density functional theory (DFT) combined with semiclassical Boltzmann transport theory, we do find that β ‐CsCu 5 Se 3 possesses ultralow lattice thermal conductivities and a high ZT value, besides the reported photovoltaic features, exhibits high thermoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“…The highest ZT reported by Zhao et al [185] for Cu 2 Te 50% Ag 2 Te is~1.8 at 727 • C. Similarly, inclusion of nanosized Ag 2 Se into Cu 2 Se increased the ZT to~0.9 at 315 • C and to~1.85 at 527 • C, according to report of Ballikaya et al [176]. In the work of Mukherjee S. [183], the incorporation of nanostructured Ag 2 Te into bulk Cu 2 Te obtained by the melting route also improved the thermoelectric properties of Cu 2 Te significantly.…”
Section: Cu 2-δ Tementioning
confidence: 81%
“…Binary copper and silver chalcogenides have excellent thermoelectric characteristics, which continue to be the subjects of intense research [2,4,82,83,109,139,[164][165][166][167]. Over the past 5 years, as examples, we can mention the works [12,14,17,31,39,99,106,129,168,169] on Cu 2-δ S, the works [15,16,165,167,[170][171][172][173][174][175][176][177][178] on Cu 2−δ Se, the works [110,[179][180][181][182][183][184][185] on Cu 2−δ Te, the works [186][187][188][189][190] on Ag 2+δ Se, the works [191][192]…”
Section: Seebeck Coefficient and Thermal Conductivity 321 Seebeck Effectmentioning
confidence: 99%
“…Ag alloying on the Cu site was further used to optimize the electrical transport properties. It is reported that the cation vacancy formation energy can be tuned in (Cu, Ag)2Te, 73,74 in which Cu2Te possesses the lowest formation energy probably due to the small Cu atomic radius. Here a similar tendency is also observed that Ag alloying in Cu6Te3S leads to the significantly increased  (Figure 8a), in coincidence with Ag alloying in Cu2Te 73 .…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…As a result, Ag alloying in Cu6Te3S enables a significant improvement of ZT (Figure 8d), the maximum ZT about 0.7 at 600 K that is comparable with the well-optimized Cu2Te based materials at the same temperature range. 73 It is highly possible that other donor dopants, such as doping with divalent ions on the Cu site or doping with halogen ions on the Te/S site, can be also effective to improve the ZT of Cu6Te3S. Besides, since Cu6Te3S based materials show an extremely low κlat, increasing the power factor by modulation doping 75 and magnetic effects 76 may be also promising for the overall enhancement of thermoelectric performance.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%